Standard ECG for differential diagnosis between Anderson-Fabry disease and hypertrophic cardiomyopathy - Vitale, Giovanni; Ditaranto, Raffaello; Graziani, Francesca; Tanini, Ilaria; Camporeale, Antonia; Lillo, Rosa; Rubino, Marta; Panaioli, Elena; Di Nicola, Federico; Ferrara, Valentina; Zanoni, Rossana; Caponetti, Angelo Giuseppe; et al. (Heart (British Cardiac Society), 2022)
OBJECTIVES: To evaluate the role of the ECG in the differential diagnosis between Anderson-Fabry disease (AFD) and hypertrophic cardiomyopathy (HCM). METHODS: In this multicentre retrospective study, 111 AFD patients with left ventricular hypertrophy were compared with 111 patients with HCM, matched for sex, age and maximal wall thickness by propensity score. Independent ECG predictors of AFD were identified by multivariate analysis, and a multiparametric ECG score-based algorithm for differential diagnosis was developed. RESULTS: Short PR interval, prolonged QRS duration, right bundle branch block (RBBB), R in augmented vector left (aVL) ≥1.1 mV and inferior ST depression independently predicted AFD diagnosis. A point-by-point ECG score was then derived with the following diagnostic performances: c-statistic 0.80 (95% CI 0.74 to 0.86) for discrimination, the Hosmel-Lemeshow χ2 6.14 (p=0.189) for calibration, sensitivity 69%, specificity 84%, positive predictive value 82% and negative predictive value 72%. After bootstrap resampling, the mean optimism was 0.025, and the internal validated c-statistic for the score was 0.78. CONCLUSIONS: Standard ECG can help to differentiate AFD from HCM while investigating unexplained left ventricular hypertrophy. Short PR interval, prolonged QRS duration, RBBB, R in aVL ≥1.1 mV and inferior ST depression independently predicted AFD. Their systematic evaluation and the integration in a multiparametric ECG score can support AFD diagnosis.
Keywords: Fabry Disease; hypertrofie levé komory srdeční; metabolic diseases; hypertrofická kardiomyopatie; diferenciální diagnóza; Diagnosis, Differential; Cardiomyopathy, Hypertrophic; genetic diseases; Electrocardiography; elektrokardiografie; inborn; Hypertrophy, Left Ventricular; electrocardiography; Retrospective Studies; blokáda Tawarova raménka; Fabryho nemoc; retrospektivní studie; hypertrophic; lidé; Humans; cardiomyopathy; Bundle-Branch Block